2013
DOI: 10.1200/jco.2012.42.8185
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Agonist for the Prevention of Chemotherapy-Induced Ovarian Failure in Patients With Lymphoma: 1-Year Follow-Up of a Prospective Randomized Trial

Abstract: A B S T R A C T PurposeTo assess the efficacy of gonadotropin-releasing hormone agonist (GnRHa) in preventing chemotherapy-induced ovarian failure in patients treated for Hodgkin or non-Hodgkin lymphoma within the setting of a multicenter, randomized, prospective trial. Patients and MethodsPatients age 18 to 45 years were randomly assigned to receive either the GnRHa triptorelin plus norethisterone (GnRHa group) or norethisterone alone (control group) concomitantly with alkylating agents containing chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 34 publications
1
88
0
5
Order By: Relevance
“…122 Some studies, including randomized trials, have evaluated the role of menstrual suppression with gonadotropin-releasing hormone (GnRH; also known as LH-releasing hormone [LHRH]) agonists to preserve ovarian function during chemotherapy. [123][124][125][126][127][128][129][130][131] Some meta-analyses have shown that GnRH agonist may be beneficial for fertility preservation. [132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition.…”
Section: Options For Femalesmentioning
confidence: 99%
“…122 Some studies, including randomized trials, have evaluated the role of menstrual suppression with gonadotropin-releasing hormone (GnRH; also known as LH-releasing hormone [LHRH]) agonists to preserve ovarian function during chemotherapy. [123][124][125][126][127][128][129][130][131] Some meta-analyses have shown that GnRH agonist may be beneficial for fertility preservation. [132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition.…”
Section: Options For Femalesmentioning
confidence: 99%
“…Another methodological error, possibly leading to inaccurate conclusions in this equivocal issue, is premature evaluation of ovarian function [1, 5-7, 10, 11, 16]. Indeed, Demeestere et al [16], who initially did not find a difference in POF rate after 1 year, have presented the 2-year follow-up of their patients [16] claiming that "the number of patients who totally restored their ovarian function was significantly higher in the GnRHa group (p 5 .049) confirming results of [anti-Müllerian hormone (AMH)]" [16]. This supports the possibility that short follow-up may be responsible for the discrepancy between studies and lead to incorrect conclusions [1].…”
Section: Discussionmentioning
confidence: 99%
“…В мировой литературе все больше внимания уделя-ется медикаментозным методам сохранения фертиль-ности, а именно использованию аГРГ с целью подав-ления овариальной функции в период проведения противоопухолевой терапии [2,4,13,16,[20][21][22][23].…”
unclassified
“…Наиболее частыми побочными эффектами являются: головные боли, частая смена настроения, бессонница, депрессия, сухость слизистых, акне, мы-шечные боли. Согласно результатам исследования, проведенного Demeestere et al, симптомы гипоэстро-гении отмечались у 75,5 % пациенток на фоне терапии аГРГ [20]. Высоковероятное снижение костной плот-ности (остеопения), развивающееся в результате гипо-эстрогенного статуса пациенток, должно учитываться при назначении препаратов данной группы, и являет-ся одним из наиболее серьезных побочных эффектов аГРГ, что в сочетании с применением стероидных гор-монов в схемах ХТ у больных лейкозами и лимфомами может стимулировать развитие аваскулярных некрозов.…”
unclassified
See 1 more Smart Citation